2012
DOI: 10.1088/0004-637x/756/2/135
|View full text |Cite
|
Sign up to set email alerts
|

Relative Orientation of Pairs of Spiral Galaxies in the Sloan Digital Sky Survey

Abstract: From our study of binary spiral galaxies in the Sloan Digital Sky Survey Data Release 6, we find that the relative orientation of disks in binary spiral galaxies is consistent with their being drawn from a random distribution of orientations. For 747 isolated pairs of luminous disk galaxies, the distribution of φ, the angle between the major axes of the galaxy images, is consistent with a uniform distribution on the interval [0With the assumption that the disk galaxies are oblate spheroids, we can compute cos … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Moon et al (2021, hereafter Paper III) proposed that SOA can be developed by interactions with neighboring galaxies. Some studies have found spin-spin alignment in interacting pairs (Mesa et al 2014;Koo & Lee 2018) although it is still controversial (Cervantes-Sodi et al 2010;Buxton & Ryden 2012;Lee 2012). This work focuses on SOA for dark matter halos with virialradius-wise interacting neighbors using a set of cosmological N -body simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al (2021, hereafter Paper III) proposed that SOA can be developed by interactions with neighboring galaxies. Some studies have found spin-spin alignment in interacting pairs (Mesa et al 2014;Koo & Lee 2018) although it is still controversial (Cervantes-Sodi et al 2010;Buxton & Ryden 2012;Lee 2012). This work focuses on SOA for dark matter halos with virialradius-wise interacting neighbors using a set of cosmological N -body simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found several types of alignments associated with galaxy pairs in which both the neighbor and the LSS play a role. First, the spins of the two galaxies in a pair tend to be preferentially aligned in the same direction (Flin 1993;Pestaña & Cabrera 2004;Slosar et al 2009;Cervantes-Sodi et al 2010;Mesa et al 2014;Koo & Lee 2018), although some controversy still remains (Oosterloo 1993;Buxton & Ryden 2012;Lee 2012). Such spin-spin alignment of galaxy pairs is generally interpreted as a result of the combined effect of the underlying LSS and the mutual interaction between paired galaxies (e.g., Sharp et al 1979;Helou 1984).…”
Section: Introductionmentioning
confidence: 99%
“…galaxy pairs remains inconclusive(Joachimi & Schneider 2010;Andrae & Jahnke 2011;Lee 2011;Buxton & Ryden 2012;Chisari et al 2015;Sifón et al 2015;Koo & Lee 2018;Krolewski et al 2019). Such alignment signals also seem to be subtly influenced by various intrinsic properties of the galaxies, including the halo mass(Li et al 2013;Trowland et al 2013;Xia et al 2017), bulge mass(Barsanti et al 2022), SF activity(Jimenez et al 2010;Shi et al 2021), and spiral morphology(Hu et al 1995;Lee 2011;Koo & Lee 2018).…”
mentioning
confidence: 99%